Macroinvertebrate distribution associated with environmental variables in alpine streams. (8th August 2022) - Becquet, Juliette; Lamouroux, Nicolas; Condom, Thomas; Gouttevin, Isabelle; Forcellini, Maxence; Launay, Bertrand; Rabatel, Antoine; Cauvy‐Fraunié, Sophie
Abstract: Ongoing hydrological alterations due to climate change and anthropogenic uses of water have major implications for freshwater biodiversity. Quantifying the relative effects of environmental variables on macroinvertebrates is required to predict biological responses to hydrological alterations. To date, no study simultaneously examined the effects of physico‐chemistry, hydraulics, and hydrology on the distribution of alpine macroinvertebrate communities and taxa. In this study, we aimed to quantify the relative correlation between these environmental variables and macroinvertebrate community composition and structure. We sampled macroinvertebrates at 66 stream sites located in three catchments in the French Alps. We characterised the proximate habitat at each site using 11 variables describing measured physico‐chemistry and hydraulics, and simulation‐based hydrology. We described relationships between community structure and the environment using a co‐inertia analysis and modelled individual taxa abundance with generalised linear mixed models. The co‐inertia revealed a significant co‐structure between the environmental and macroinvertebrate matrices. Glacier‐influenced sites with high turbidity and summer flow exhibited similar community composition with low total abundance. Sources at high altitude and sites with low glacial influence, exhibiting high summer flow and flow velocity, were dominated by Diamesinae, Rhithrogena spp., Dictyogenus spp., and Baetis alpinus . Streams fed by rainfall/snowmelt and valley sources, associated with higher temperature, conductivity, and monthly discharge variability were characterised by higher richness and abundances. Models indicated that the three types of proximate habitat variables significantly contributed to the macroinvertebrate distribution. Turbidity was strongly negatively associated with macroinvertebrate abundances. Increasing flow velocity and summer flow had significant (mainly negative) effect in 43% of models. The co‐structure between communities and proximate habitat variables was shared by the three catchments. For most individual taxa, catchment identity did not influence abundance models and cross‐validations indicated transferable effects of proximate habitat variables among alpine catchments. Our results can be used to infer responses of alpine macroinvertebrates to multivariate environmental changes. Understanding the relationships between macroinvertebrates and environmental variables help to predict how communities and taxa will be affected by habitat alterations due to ongoing hydrological changes and resulting physico‐chemical conditions.